Visual transformation for guidelines presentation of the strength of recommendations and the certainty of evidence - Klugar, Miloslav; Kantorová, Lucia; Pokorná, Andrea; Líčeník, Radim; Dušek, Ladislav; Schünemann, Holger J; Riad, Abanoub; Kantor, Jiří; Klugarová, Jitka (Journal of clinical epidemiology, 2022)
OBJECTIVE: The objective of this paper is to propose an approach to visual unification of adapted guidelines and transformation of classifications of certainty of evidence (CoE) and strength of recommendations (SoR) into the approach suggested by the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) working group. STUDY DESIGN AND SETTING: We carried out a literature search in MEDLINE and Epistemonikos, an analysis of selected guidelines, and an iterative discussion to decide on a consistent visual presentation and CoE and SoR depictions. RESULTS: The results of the literature search suggested this issue had not been addressed yet. The analysis of the chosen eight guidelines showed significant heterogeneity in the visual presentation of recommendations. Recommendations were often worded similarly to whether or not they were strong or conditional. Many guidelines contained "statements," almost all of which did not fulfill the good practice statement (GPS) criteria. We proposed an approach for transforming recommendations that are being adapted and which use various classification systems for CoE and SoR into GRADE and a consistent visual style. CONCLUSION: Guideline developers should aim for unification in the formulation of recommendations to improve transferability.
Keywords: Publications; Visual style; medicína založená na důkazech; systém GRADE; GRADE; Good practice statements; Strength of recommendations; Humans; lidé; Clinical practice guidelines; Certainty of evidence; Evidence-Based Medicine; GRADE Approach; publikace